Forças óticas em guias de onda acoplados e fabricação de nano-ilhas de MoS2 via SPM - Thales Fernando Damasceno Fernandes (2018)
This thesis is divided into two parts: in the first part, we have studied integrated photonics and optical forces in coupled waveguide systems and, in the second part, the tuning in the optical properties of 2D semiconductors. For the first part, a detailed study of the optical forces, that appear in coupled waveguide systems, is made, where we explained and calculated correctly the beating force that appears in this system. Where this force, until then, was ignore or badly interpreted in the literature. This optical force differs drastically from the usual optical forces in this type of system, which can be either attractive or repulsive. The beating force is neither attractive nor repulsive, but it can acts in the center of mass of the system, thus, making it possible to accelerate the waveguides in a certain direction. The origin of this beating force is due to transverse moment transfer occurring in coupled waveguides when they are excited in a superposition eigenmodes. This way, the energy will oscillate between one waveguide and another, which will generate a momentum exchange between light and matter and, consequently, a force in the waveguides. The study of this force was performed both analytically and by finite element simulations (FEM - Finite Element Method) and it was observed that this force varies with the direction of propagation. As the force in electromagnetic systems varies with the square of the electromagnetic fields, when a sum of modes of the system is excited, there will always be a beating in the system. Explicit calculations of this optical force agree very well with the heuristics conception derived from the momentum transfer between the waveguides. Our results demonstrate that in this type of system the associated moment is probably Minkowski¿s one. v Later, the calculation of the beating force is generalized for the case of curved waveguides with arbitrary superpositions and compared with different force models, where it was shown the main differences among the models. For the second part of this work, Local Anodic Oxidation (LAO) was used via scanning probe microscopy (SPM) techniques to oxidize multilayer MoS2. It was seen that without a fine tuning of the LAO process it is possible to create MoS2 monolayers of varying sizes, geometries, and positioning. These monolayers are covered with molybdenum oxide, creating a MoS2-MoO3 heterostructure. It has been observed that in these heterostructures, there is an increase in luminescence (PL) of up to two orders of magnitude. The origin of this increase is related to the charges withdrawal from MoS2 by MoO3, thus making the MoS2 emission predominantly originated from neutral excitons rather than trions, which consists of a much more efficient emission.